Estenosis carotídea en pacientes con enfermedad cerebrovascular isquémica - Vásquez García Reyna Melchora (2016)
Introduction: Most ischemic strokes are attributed to atherosclerotic disease of the carotid arteries. This study aimed to establish the number of patients with ischemic cerebrovascular disease (CVD) having carotid artery stenosis. Materials and Methods: A cross-sectional study, descriptive and observational was performed. A total of 71 patients with ischemic stroke of the Neurology Service were included in the study, who had carotid doppler ultrasound report, and were treated at the Hospital Belen of Trujillo, during the period 2010-2015. The gradation of carotid artery stenosis was then determined, following the criteria procedures recommended by the Spanish Society of Neurology. Finally a statistical program for the creation of tables and graphs was used. Results: All patients included in the study presented carotid artery stenosis. The average age of patients was 69.7 years (SD = 13.5), the majority was women (54%). the most common type of disease was: atherothrombotic cerebral infarction (69%). The most common risk factor was: Hypertension (62%) and the most common degree of carotid artery stenosis was: Mild (78.9%). Conclusion: Carotid artery stenosis is strongly related to the EVC, all patients in the present study had carotid artery stenosis